DIARRHEA PREVENTION PRACTICES AMONG CARETAKERS OF UNDER FIVE CHILDREN IN TANZANIA: A CROSS-SECTIONAL STUDY - Kinemelo, Erasto; Nsongoma, Daniel (Journal of Public Health Research and Community Health Development, 2025)
Background: Diarrhea remains the second leading public health concern, affecting children under the age of five. The World Health Organization stipulates that diarrhea diseases are responsible for approximately each year 801,000 deaths of children under five years old due to avoidable diarrhea diseases. Purpose: The purpose of this study was to assess Practices on Prevention of Diarrhea Disease to under Five Children Cared by Caretakers at Hombolo Ward in Dodoma, Tanzania. Methods: Cross sectional study design was used, quantitative approach was employed, 116 participants were included, stratified random sampling was used to select four strata and simple random technique was used from each stratum, questionnaires and observation methods were used to collect data among caretakers. Data analysis used Social Package Statistical Science (SPSS). Results: The findings indicate that 64.6% of the caretakers of under five children had moderate knowledge about diarrhea diseases, causes, symptoms and complications of diarrhea. Approximately 68.3 % of the caretakers had a positive attitude towards prevention of diarrhea, while 31.7 % had a negative attitude. Furthermore, it was revealed that in practice, for example,74.1% of caretakers failed to specify the methods they use to treat drinking water. Conclusion: The study concludes that the caretakers had moderate knowledge. Also, the caretakers had positive attitudes towards prevention of diarrhea. However, knowledge on diarrhea disease was not related to preventive practices as most caretakers with good knowledge often had poor preventive practices.